The Next Decade : Where We Have Been and Where We are Going - Friedman, George (New York Doubleday, 2011)
The author of the book "The Next 100 Years" now focuses his geopolitical forecasting acumen on the next decade and the imminent events and challenges that will test America and the world, specifically addressing the skills that will be required by the decade's leaders. From Islam's decline to China's financial crisis, he offers a number of scenarios and predictions.
Keywords: World politics -- 21st century -- Forecasting. -- World politics -- Forecasting